(untitled) (Zoo Botanica, 2025)
Edible coatings offer a sustainable solution to extend the shelf life and maintain the quality of perishable foods like Labeo rohita (Rohu) fillets. Rohu is particularly susceptible to quality degradation caused by lipid oxidation, enzymatic activity, and moisture loss. This study investigated the production and application of whey protein-based films on the physicochemical and sensory quality of L. rohita (Rohu) fillets during refrigerated storage (4 ± 1 °C) for 15 days. Coating formulations were prepared using whey protein isolate (WPI) and whey protein concentrate (WPC) in combination with glycerol and gelatin at different ratios: WPI + Glycerol (1:1), WPI + Glycerol (1:2), WPI + Glycerol + Gelatin (1:1:1), WPC + Glycerol (1:1), and WPC + Glycerol (1:2). Coatings were applied by dipping, and fillets were analyzed for pH, weight loss, color, texture, and aroma for 15 days. Data were statistically analyzed using one-way ANOVA followed by Tukey’s test (p < 0.05). Significant differences were observed among treatments. The WPC+Glycerol (1:2) coating demonstrated the highest preservation efficiency, maintaining pH (6.33 ± 0.25), minimizing weight loss (16.4 %), and retaining desirable texture (3.33 ± 1.15) and color (2.67 ± 1.15) scores throughout storage. In contrast, uncoated samples showed rapid spoilage with extreme hardness, darkening, and off-odor. These findings confirm that WPC-based coatings, especially at a 1:2 ratios with glycerol are benefical since they could extend the shelf life of food products by reducing respiration rates, and they outperform alternative biopolymeric packaging.